Evaluation of Parthenocarpic Cucumber (Cucumis sativus L.) Cultivars for Summer Cultivation under Insect-Proof Net House in Indian Hot Arid Region - Nirmala; Choudhary, Santosh (Annals of Arid Zone, 2023)
Protected cultivation of cucumber (Cucumis sativus L.) is gaining ground on a commercial scale in arid-western parts of India. The summer cultivation of cucumber is highly remunerative due to high market price. In the present investigation, eight commercial parthenocarpic cucumber cultivars were evaluated for growth, yield and quality traits under insect-proof net house condition in arid region of Rajasthan during 2017. Results revealed that the significantly higher vine length (332.00 cm) and stem diameter (0.53 cm) was observed in hybrid ‘Ruchi-707’, whereas the maximum leaf area (418.00 cm2) was noted in ‘Aviva’. Hybrid ‘Aviva’ took minimum number of days to flowering (29.00 days) and first fruit set (32.40 days), while ‘Ruchi 707’ was observed earliest in first fruit maturity (38.3 days) as well as longest in crop duration (97.3 days). Hybrid ‘Aviva’ was also recorded the highest number of flowers vine-1 (38.5), fruit volume (360 cm3), fruit weight (228.00 g), TSS (5.73oBrix) and ascorbic acid content (3.58 mg 100g-1 FW). However, ‘Ruchi-707’ was observed with the highest number of fruits per vine (16.5), fruit yield per vine (3.74 kg) and fruit yield per 500 m2 (11.57 t) and longest shelf-life (5.5 days). The fruit yield per vine had a significant positive correlation with average fruit weight (r= 0.891**), and crop duration (r=0.893**) and significant negative correlation with the number of fruits per vine (r= -0.844**). Hybrid ‘Ruchi 707’ also fetched the highest net returns (Rs. 2,45,642) and B:C ratio (5.62) per 500 m2 . Based on earliness, fruit yield and commercial quality, hybrid ‘Ruchi 707’ followed by ‘Aviva’ were found suitable for summer production in the arid region of Rajasthan.